D.A. PETROVSKY'S INITIATIVES FOR THE RESTORATION OF CADET CORPS IN THE RSFSR (1921-1924) - Solovyev R.A. (Вестник Брянского государственного университета)
The article is devoted to one of the most poorly studied episodes in the history of the Russian military school – the work of the head of the Main Directorate of Military Educational Institutions (GUVUZ) D.A. Petrovsky on the reconstruction of the cadet corps system in the RSFSR. The need to equip the army and navy with well-trained command personnel in the early 1920s put on the agenda the question of the expediency of reviving military preparatory educational institutions. The initiator of this was D.A. Petrovsky. His articles and speeches pointed out the ideological inconsistency and the anti-national nature of military training for teenagers in the pre-revolutionary period, but at the same time he found positive sides in it. The paper reveals the content of his proposals, shows the chronology of events, the motives that prompted the head of the GUVUZ to turn to the experience of cadet corps. The idea of D.A. Petrovsky was actively opposed by the People's Commissariat of Education of the RSFSR, which controlled not only the activities of educational institutions, but also carried out the leadership of ideological work in the republic. It was in the ideological sphere that the confrontation between the two departments lay on the issue of the revival of cadet education. D.A. Petrovsky maneuvered, looked for new forms and ways to implement his idea. Eventually, military preparatory educational institutions for teenagers were opened in the USSR, but this happened after the resignation of D.A. Petrovsky from the post of Head of the GUVUZ.